"I'm a Mac" versus "I'm a PC": Personality Differences between Mac and PC Users in a College Sample. Issue 1 (January 2014) - Nevid, Jeffrey S.; Pastva, Amy; Cohen, Ronald Jay
ABSTRACT One hundred eight college students who had purchased either a Mac or PC laptop computer completed measures of the Big Five personality traits, ratings of brand characteristics of Macs and PCs, measures of implicit attitudes toward these products, and determinants of brand choices. Big Five personality traits did not differentiate between Mac and PC owners. Students overall rated Macs higher on various product attributes (attractive style, cool, youthful, and exciting) and PCs higher on reasonable price and good for gaming. Brand owners rated their own brands higher on characteristics of reliability, good for homework, ease of use, good for Internet surfing, and good features. PC owners placed greater importance on cost as a determinant of brand choice, whereas Mac owners placed greater emphasis on style. Personality traits may have more nuanced effects on brand choices, as shown by relationships between Neuroticism and greater importance placed on cost and lesser importance placed on ease of use. Openness to Experience was associated with greater importance placed on reliability and lesser importance placed on style. Supporting the predictive validity of the Implicit Association Test (IAT) in predicting consumer preferences, Mac owners showed more favorable implicit attitudes and stronger implicit self‐identification with Macs than did PC owners. Implicit attitudes also predicted self‐reported ratings of various product characteristics.